THE MAIN DIRECTIONS OF ENSURING THE ENVIRONMENTAL SAFETY OF WATER BODIES IN TRANSBOUNDARY BASINS - Ayzhan, Zhatkanbaeva; Arаilym, Jangabulova; Kulyash, Aydarkhanova; Dina, Baimakhanova; Haifeng, Zhao (Scientific Journal of Pedagogy and Economics, 2020)
The article is devoted to the analysis of priority areas of international cooperation in the field of ensuring environmental safety of transboundary water bodies. The authors of the article indicated such areas of environmental safety as: Water-energy problem of the Central Asian countries; impact of climate change on water; Aral ecological crisis and its consequences for the natural environment of the Central Asian region. The authors of the article made recommendations on eliminating the environmental problems of transboundary water bodies. It is proposed to sign fundamental documents on legal issues of water allocation and protection of transboundary rivers on the basis of international law and bring the problem of transboundary rivers to the level of the SCO and tripartite negotiations (Russia, Kazakhstan, China). The necessity of building joint hydropower facilities on transboundary rivers is substantiated. The authors propose to expand, improve and modernize the control network (gauging stations, etc.) in all river basins of Kazakhstan and China.